The Impact of institutions on structural change in manufacturing : the case of international trade regime in textiles and clothing - Memedovic, Olga (UNIDO ViennaAT, 2010)
Compares the ex-ante simulation estimates with real trade data flows four years after the ending of the quota-based regime in the textile and clothing sectors. Aims to contribute to better understanding of how international rules on trade can affect the dynamics of division of labour and structural changes in industry and how these processes need to be more closely monitored.